2006
DOI: 10.2754/avb200675010021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Prolonged Melatonin Administration and Short-Term Fasting in Laboratory Rats

Abstract: Bojková B., M. Marková, E. Ahlersová, I. Ahlers, E. Adámeková, P. Kubatka, M. Kassayová: Metabolic Effects of Prolonged Melatonin Administration and Short-Term Fasting in Laboratory Rats. Acta Vet. Brno 2006, 75: 21-32.The aim of this work was to evaluate the effect of prolonged administration of the pineal hormone melatonin and short-term fasting on metabolic variables in male and female Wistar:Han rats. Melatonin (MEL, 4µg/ml of tap water) was administered daily since the 5 th week of age. The control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…For exam ple, an increase in the incidence of pancreatic diabetes incidence was observed in the hereditary hypertrophy of the PG. According to several authors, this was mediated by an increase in the tolerance to glucose and a decrease in insulin synthesis [28].…”
Section: Functional Changes In the Pg With Agingmentioning
confidence: 99%
“…For exam ple, an increase in the incidence of pancreatic diabetes incidence was observed in the hereditary hypertrophy of the PG. According to several authors, this was mediated by an increase in the tolerance to glucose and a decrease in insulin synthesis [28].…”
Section: Functional Changes In the Pg With Agingmentioning
confidence: 99%
“…In addition, recent studies have shown that melatonin influences carbohydrates and lipid metabolism in goldfish liver and muscle 17 ; inconsistent results, instead, were found in mammals. [21][22][23] In this regard, among signals that regulate feeding behavior and metabolism, leptin (LPT) plays a key role as a satiety molecule controlling body weight maintenance. In both mammals and fish, LPT is secreted by a variety of tissues such as adipocytes, stomach, muscle, placenta, and brain, [24][25][26][27] and its anorexigenic action is exerted by stimulating melanocyte-stimulating hormone and subsequently MC4R, the key receptor in appetite regulation of the melanocortin system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on the relationship between melatonin and carbohydrate and lipid metabolism in mammals have provided inconsistent results. Particularly, the effects on the glucose metabolism and the underlying mechanisms remain to be elucidated [9, 17]. Hypoglycemia, hyperglycemia [9] and no effect [10, 25] after melatonin administration have been reported in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the effects on the glucose metabolism and the underlying mechanisms remain to be elucidated [9, 17]. Hypoglycemia, hyperglycemia [9] and no effect [10, 25] after melatonin administration have been reported in rats. The effect of melatonin on lipid metabolism can also vary depending on the experimental conditions, and both reductions [25, 26] and increases [9] in liver and plasma lipids have been reported.…”
Section: Introductionmentioning
confidence: 99%